Effect of the tip state during qPlus noncontact atomic force microscopy of Si(100) at 5 K: Probing the probe - Sweetman, Adam; Jarvis, Sam; Danza, Rosanna; Moriarty, Philip (Beilstein Journal of Nanotechnology, 2012)
Background: Noncontact atomic force microscopy (NC-AFM) now regularly produces atomic-resolution images on a wide range of surfaces, and has demonstrated the capability for atomic manipulation solely using chemical forces. Nonetheless, the role of the tip apex in both imaging and manipulation remains poorly understood and is an active area of research both experimentally and theoretically. Recent work employing specially functionalised tips has provided additional impetus to elucidating the role of the tip apex in the observed contrast.Results: We present an analysis of the influence of the tip apex during imaging of the Si(100) substrate in ultra-high vacuum (UHV) at 5 K using a qPlus sensor for noncontact atomic force microscopy (NC-AFM). Data demonstrating stable imaging with a range of tip apexes, each with a characteristic imaging signature, have been acquired. By imaging at close to zero applied bias we eliminate the influence of tunnel current on the force between tip and surface, and also the tunnel-current-induced excitation of silicon dimers, which is a key issue in scanning probe studies of Si(100).Conclusion: A wide range of novel imaging mechanisms are demonstrated on the Si(100) surface, which can only be explained by variations in the precise structural configuration at the apex of the tip. Such images provide a valuable resource for theoreticians working on the development of realistic tip structures for NC-AFM simulations. Force spectroscopy measurements show that the tip termination critically affects both the short-range force and dissipated energy.
Keywords: force spectroscopy; image contrast; noncontact AFM; qPlus; Si(001); Si(100); tip (apex) structure

(untitled) - Giessibl, F. J. (Rev. Mod. Phys., 2003)

(untitled) - Giessibl, F. J.; Hembacher, S.; Bielefeldt, H.; Mannhart, J. (Science, 2000)

(untitled) - Lantz, M. A.; Hug, H. J.; Hoffmann, R.; van Schendel, P. J. A.; Kappenberger, P.; Martin, S.; Baratoff, A.; Güntherodt, H.-J. (Science, 2001)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Sugimoto, Y.; Pou, P.; Custance, Ó.; Jelinek, P.; Morita, S.; Pérez, R.; Abe, M. (Phys. Rev. B, 2006)

(untitled) - Naitoh, Y.; Kinoshita, Y.; Li, Y. J.; Kageshima, M.; Sugawara, Y. (Nanotechnology, 2009)

(untitled) - Oyabu, N.; Pou, P.; Sugimoto, Y.; Jelinek, P.; Abe, M.; Morita, S.; Pérez, R.; Custance, Ó. (Phys. Rev. Lett., 2006)

(untitled) - Enevoldsen, G. H.; Pinto, H. P.; Foster, A. S.; Jensen, M. C. R.; Kühnle, A.; Reichling, M.; Hofer, W. A.; Lauritsen, J. V.; Besenbacher, F. (Phys. Rev. B, 2008)

(untitled) - Uda, T.; Shigekawa, H.; Sugawara, Y.; Mizuno, S.; Tochihara, H.; Yamashita, Y.; Yoshinobu, J.; Nakatsuji, K.; Kawai, H.; Komori, F. (Prog. Surf. Sci., 2004)

(untitled) - Canova, F. F.; Foster, A. S. (Nanotechnology, 2011)

(untitled) - Ghasemi, S. A.; Goedecker, S.; Baratoff, A.; Lenosky, T.; Meyer, E.; Hug, H. J. (Phys. Rev. Lett., 2008)

(untitled) - Pou, P.; Ghasemi, S. A.; Jelinek, P.; Lenosky, T.; Goedecker, S.; Perez, R. (Nanotechnology, 2009)

(untitled) - Wolkow, R. A. (Phys. Rev. Lett., 1992)

(untitled) - Yoshida, S.; Kimura, T.; Takeuchi, O.; Hata, K.; Oigawa, H.; Nagamura, T.; Sakama, H.; Shigekawa, H. (Phys. Rev. B, 2004)

(untitled) - Li, Y. J.; Nomura, H.; Ozaki, N.; Naitoh, Y.; Kageshima, M.; Sugawara, Y.; Hobbs, C.; Kantorovich, L. (Phys. Rev. Lett., 2006)

(untitled) - Arai, T.; Tomitori, M. (Applied Surface Science, 2000)

(untitled) - Weymouth, A. J.; Wutscher, T.; Welker, J.; Hofmann, T.; Giessibl, F. J. (Phys. Rev. Lett., 2011)

(untitled) - Sagisaka, K.; Fujita, D.; Kido, G. (Phys. Rev. Lett., 2003)

(untitled) - Sweetman, A.; Jarvis, S.; Danza, R.; Bamidele, J.; Gangopadhyay, S.; Shaw, G. A.; Kantorovich, L.; Moriarty, P. (Phys. Rev. Lett., 2011)

(untitled) - Sweetman, A.; Jarvis, S.; Danza, R.; Bamidele, J.; Kantorovich, L.; Moriarty, P. (Phys. Rev. B, 2011)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 2000)

(untitled) - Sweetman, A.; Gangopadhyay, S.; Danza, R.; Berdunov, N.; Moriarty, P. (Appl. Phys. Lett., 2009)

(untitled) - Chen, C. J. (Nanotechnology, 2006)

(untitled) - Woolley, R. A. J.; Stirling, J.; Radocea, A.; Krasnogor, N.; Moriarty, P. (Appl. Phys. Lett., 2011)

(untitled) - Sweetman, A.; Danza, R.; Gangopadhyay, S.; Moriarty, P. (J. Phys.: Condens. Matter, 2011)

(untitled) - Kobayashi, K.; Yamada, H.; Horiuchi, T.; Matsushige, K. (Appl. Surf. Sci., 2000)

(untitled) - Rahe, P.; Bechstein, R.; Schütte, J.; Ostendorf, F.; Kühnle, A. (Phys. Rev. B, 2008)

(untitled) - Liu, Z.; Zhang, Z.; Zhu, X. (Phys. Rev. B, 2008)

(untitled) - Such, B.; Glatzel, T.; Kawai, S.; Koch, S.; Meyer, E. (J. Vac. Sci. Technol., B, 2010)

(untitled) - Campbellová, A.; Ondráček, M.; Pou, P.; Pérez, R.; Klapetek, P.; Jelínek, P. (Nanotechnology, 2011)

(untitled) - Sawada, D.; Sugimoto, Y.; Morita, K.; Abe, M.; Morita, S. (Appl. Phys. Lett., 2009)

(untitled) - Sader, J. E.; Jarvis, S. P. (Appl. Phys. Lett., 2004)

(untitled) - Ternes, M.; González, C.; Lutz, C. P.; Hapala, P.; Giessibl, F. J.; Jelínek, P.; Heinrich, A. J. (Phys. Rev. Lett., 2011)